Off-farm employment increases women's empowerment: Evidence from rice farms in the Philippines - Maligalig, Rio; Demont, Matty; Umberger, Wendy J.; Peralta, Alexandra (Elsevier, 2019)
We examined intrahousehold decision making with respect to household investment in portfolios of future rice varietal trait improvements (VTIs) to increase farm households' livelihoods in Nueva Ecija, Philippines. Investment decisions were elicited using an experimental methodology based on investment games. In the investment game, couples from rice farming households were given the opportunity to invest in public rice breeding. They selected, first individually, and then jointly, a replacement rice variety to improve upon and were then asked to allocate a research endowment fund to a portfolio of VTIs. We developed a novel indicator of women's intrahousehold decision-making power (WIDMP) based on the relative Euclidean distances between the individual and joint VTI portfolios. We found that WIDMP is normally distributed; and that, on average, women had almost equal (48%) decision-making power as men (52%), revealing almost perfect gender equity in investment decision making in rice breeding. Women were slightly more empowered if they were engaged in off-farm employment and were less experienced in farming. More empowered women had a higher discount factor and based their investment decisions on anticipated future trends, rather than current or past experience. The findings not only highlight the importance of considering gender roles in technology design, adoption and extension programs, but also have broader implications in terms of women empowerment programs. Consistent with the Sustainable Development Goals (SDGs), our evidence suggests that education and training programs need to be paired with investments generating off-farm employment opportunities to effectively increase women's bargaining power in the household